2018
DOI: 10.1038/s41598-018-33310-4
|View full text |Cite
|
Sign up to set email alerts
|

MiR-323b-5p acts as a novel diagnostic biomarker for critical limb ischemia in type 2 diabetic patients

Abstract: Type 2 diabetes mellitus (T2DM) is a major contributor to peripheral artery disease (PAD), especially in cases that advance to critical limb ischemia (CLI). Accumulating evidence indicates that miRNAs play an important role in the development of PAD and T2DM. Due to the limited value of current diagnostic methods for CLI in T2DM patients, we compared the miRNA expression profiles of Chinese T2DM patients with or without CLI to find out whether distinctive miRNAs could serve as potential diagnostic biomarkers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 60 publications
1
15
1
1
Order By: Relevance
“…Other studies have also explored the use of circulating miRNA as potential biomarkers for CLTI but reached vastly different conclusions to the findings from this study. For instance, Li et al and Cheng et al have previously identified miRNA-4739 and miRNA-323b-5p as potential biomarkers of CLTI in patients with type-2 diabetes, respectively [26,27]. However, our findings do not demonstrate the overexpression of miRNA-4739 or miRNA-323b-5p in CLTI patients when compared to non-PAD patients.…”
Section: Discussioncontrasting
confidence: 89%
“…Other studies have also explored the use of circulating miRNA as potential biomarkers for CLTI but reached vastly different conclusions to the findings from this study. For instance, Li et al and Cheng et al have previously identified miRNA-4739 and miRNA-323b-5p as potential biomarkers of CLTI in patients with type-2 diabetes, respectively [26,27]. However, our findings do not demonstrate the overexpression of miRNA-4739 or miRNA-323b-5p in CLTI patients when compared to non-PAD patients.…”
Section: Discussioncontrasting
confidence: 89%
“…The latter is associated with Parkinson's disease ( 50 ), but the roles of the two miRNAs in CVDs have not been studied. Target loss with rs4695253 was predicted for six miRNAs: MiR-1264 was upregulated in the circulation 3 h after ischemia ( 51 ) and critical limb ischemia in T2DM ( 52 ), and downregulated in neuroglioma ( 53 ). MiR-550a-3p was downregulated in myelodysplastic syndromes ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating studies have highlighted the diagnostic potential of aberrant miRNAs in various human diseases [ 29 , 30 ]. The clinical significance of miR-136 in disease diagnosis has also been reported in some diseases.…”
Section: Discussionmentioning
confidence: 99%